2015
DOI: 10.1142/s0218271815440149
|View full text |Cite
|
Sign up to set email alerts
|

A Second Law for higher curvature gravity

Abstract: The Second Law of black hole thermodynamics is shown to hold for arbitrarily complicated theories of higher curvature gravity, so long as we allow only linearized perturbations to stationary black holes. Some ambiguities in Wald's Noether charge method are resolved. The increasing quantity turns out to be the same as the holographic entanglement entropy calculated by Dong. It is suggested that only the linearization of the higher-curvature Second Law is important, when consistently truncating a UV-complete qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
219
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(244 citation statements)
references
References 45 publications
(95 reference statements)
8
219
0
Order By: Relevance
“…As discussed in [39,40] the holographic entanglement entropy functionals serve as a good starting point to examine the second law for higher derivative black hole entropy. The discussion thus far has been confined to the linear response regime of small amplitude fluctuations away from equilibrium.…”
Section: Jhep11(2016)028mentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in [39,40] the holographic entanglement entropy functionals serve as a good starting point to examine the second law for higher derivative black hole entropy. The discussion thus far has been confined to the linear response regime of small amplitude fluctuations away from equilibrium.…”
Section: Jhep11(2016)028mentioning
confidence: 99%
“…These solutions are completely real in the Rindler wedges, but, for even q, they might present some imaginary phases in the Milne wedges. 40 Once one has a solution, after regularizing the bulk properly, one should be able to compute the action. This procedure was carried out explicitly in d = 2 from the Euclidean perspective in [38,44], although the explicit evaluation of this action is far from being trivial because (among other things) of the regularization of the bulk.…”
Section: A Bulk Evaluation Of the Rényi Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…Using this property, by analogy with the JM entropy of the purely Lovelock gravity, we introduce a new formula of the entropy after adding the scalar field and showed that this JM entropy increases in Vaidya-like black hole solution for the scalar-hairy Lovelock gravity under first-order approximation. Moreover, we showed that different from the entropy in F (Riemann) gravity obtained in [29], here the difference between the JM entropy and Wald entropy contains the correction from the scalar field.…”
Section: Discussionmentioning
confidence: 52%
“…If we restrict attention to linearized metric perturbations to stationary black holes, it has been shown that the Jacobson-Myers (JM) entropy of the Lovelock gravity and the holographic entropy of quadratic curvature gravity obey the second law [25][26][27][28]. More generally, Wall gave a general method to evaluate the corrected entropy which satisfies the linearized second law and showed that it takes the form [29]…”
Section: Introductionmentioning
confidence: 99%